2016
DOI: 10.3758/s13414-016-1219-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of absolute luminance and luminance contrast on visual discrimination in low mesopic environments

Abstract: Recent research revealed considerable decline in visual perception under low luminance conditions. However, systematic studies on how visual performance is affected by absolute luminance and luminance contrast under low mesopic conditions (<0.5 cd/m) is lacking. We examined performance in a simple visual discrimination task under low mesopic luminance conditions in three experiments in which we systematically varied base luminance and luminance contrast between stimulus and background. We further manipulated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…There was a reduction in CS with MTF CL compared to control, and a greater reduction was found when wearing the ND filter. The results agree with findings that CS is reduced with decreased luminance, 29 as would be the case when wearing ND filters. Studies also pointed out that target discrimination and identification are also affected, 30 so that reaction time decreased with low luminance.…”
Section: Discussionsupporting
confidence: 90%
“…There was a reduction in CS with MTF CL compared to control, and a greater reduction was found when wearing the ND filter. The results agree with findings that CS is reduced with decreased luminance, 29 as would be the case when wearing ND filters. Studies also pointed out that target discrimination and identification are also affected, 30 so that reaction time decreased with low luminance.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Hunter and colleagues demonstrated a deficiency window and performance efficiency functions for performance accuracy (d') and reaction time for a simple twotarget discrimination task under low mesopic conditions (Hunter, Godde, & Olk, 2016). Participants had to identify a target within a two-stimuli search array with absolute target luminance, luminance contrast, and target eccentricity being manipulated.…”
mentioning
confidence: 99%
“…Because of our previous study being restricted to a simple two-target discrimination task and simplified analyses, it is necessary to apply similar procedures in a more complex visual-search paradigm to obtain a clearer picture of the hypothesized mechanisms and a more robust assessment of the performance efficiency functions (Hunter et al, 2016). In the present study, we therefore raised the questions (1) whether the deficiency window and the performance efficiency functions described in our previous study (Hunter et al, 2016) could be demonstrated under low luminance conditions also in visual-search tasks of different complexity, and, if so, (2) how the introduced efficiency functions describing the contributions of C M or C W to performance need to be adjusted for these conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations